2011
DOI: 10.2174/156720511794604543
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes: Implications for Neuroinflammatory Pathogenesis of Alzheimers Disease

Abstract: Alzheimer's disease (AD) is a neurodegenerative disease with major clinical hallmarks of memory loss, dementia, and cognitive impairment. Neuroinflammation is involved in the onset of several neurodegenerative disorders. Astrocyte is the most abundant type of glial cells in the central nervous system (CNS) and appears to be involved in the induction of neuroinflammation. Under stress and injury, astrocytes become astrogliotic leading to an upregulation of the expression of proinflammatory cytokines and chemoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
151
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(162 citation statements)
references
References 205 publications
(303 reference statements)
5
151
0
6
Order By: Relevance
“…Although most research has focused on the effect of Tau protein tangles and A␤ plaques on neuronal function and survival, it is now well established that astrocytes also play a role in AD pathology (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). In the CNS, astrocytes are indispensable for the support of neurons.…”
Section: Alzheimer Disease (Ad)mentioning
confidence: 99%
See 1 more Smart Citation
“…Although most research has focused on the effect of Tau protein tangles and A␤ plaques on neuronal function and survival, it is now well established that astrocytes also play a role in AD pathology (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). In the CNS, astrocytes are indispensable for the support of neurons.…”
Section: Alzheimer Disease (Ad)mentioning
confidence: 99%
“…In the CNS, astrocytes are indispensable for the support of neurons. However, astrocytes can also adopt an activated state where they start to migrate and proliferate and induce inflammatory and proapoptotic cell signaling pathways (8,10,15,16). Astrocytic reactivation has been observed in many neurodegenerative diseases, including AD, and is thought to occur as a response to oxidative stress and cytokine release (8, 10 -12, 16 -18).…”
Section: Alzheimer Disease (Ad)mentioning
confidence: 99%
“…In neurodegeneration models, early stages are often associated with atrophy of astroglia, whereas later, astrocytosis and astrocyte activation contribute to the neuroinflammatory component of neurodegeneration. 42,43 Noteworthy, it was shown that proNGF produced by reactive astrocytes in response to oxidative stress promotes motoneuron death in a p75…”
mentioning
confidence: 99%
“…Although APP and S100B have previously been implicated in oxidative stress and cell death, constitutive over-expression of these and other HSA21 genes would also predict upregulation of inflammatory responses (astrocytosis), leading to a skewed gliocentric progenitor phenotype. The ongoing cell death and inflammation from APP and S100B promote reactive astrocytosis and astrocytes secrete S100B, causing further cell injury and death (Li et al, 2011). This same mechanism of injury in the mature brain could also take place within the progenitor population during development.…”
Section: Combinatorial Gene Effects In Ds Hnps Contribute To the Ds Pmentioning
confidence: 99%